2019
DOI: 10.5796/electrochemistry.19-00022
|View full text |Cite
|
Sign up to set email alerts
|

Hard X-ray Photoelectron Spectroscopy Analysis of Surface Chemistry of Spray Pyrolyzed LiNi<sub>0.5</sub>Co<sub>0.2</sub>Mn<sub>0.3</sub>O<sub>2</sub> Positive Electrode Coated with Lithium Boron Oxide

Abstract: It is known that the deterioration of LiNi 0.5 Co 0.2 Mn 0.3 O 2 is suppressed by inhibiting direct contact between the cathodes and the electrolyte by surface coating. In order to evaluate the influence of the electrode/electrolyte interface degradation, it is necessary to eliminate the influence of particle cracking. In this study, LiNi 0.5 Co 0.2-Mn 0.3 O 2 particles with a small size (500 nm to 1 µm) without crack formation after charge-discharge cycling were synthesized by a spray pyrolysis method. Hard X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Therefore, lithium-ion conductors have been developed as alternative coating materials. Hashigami et al prepared lithium boron oxide (LBO)-coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 by an antisolvent precipitation method [186]. XRD results indicated that the diffraction peak intensity ratio of the (003) to the (104) decreased by the coating of LBO.…”
Section: The Group Iiia Metal Oxides (Mox M = B Al)mentioning
confidence: 99%
“…Therefore, lithium-ion conductors have been developed as alternative coating materials. Hashigami et al prepared lithium boron oxide (LBO)-coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 by an antisolvent precipitation method [186]. XRD results indicated that the diffraction peak intensity ratio of the (003) to the (104) decreased by the coating of LBO.…”
Section: The Group Iiia Metal Oxides (Mox M = B Al)mentioning
confidence: 99%
“…31,[36][37][38][39][40][41] And during high-pressure operation and long-term cycling, intercrystalline cracks can easily diffuse to the particle surface, leading to structural collapse and cycle degradation. [42][43][44][45][46][47] In that case, a series of problems, such as the irreversible phase transition, the side reaction on interface, and the heterogeneity of secondary particles may appear on the crystal surface of NCM cathode when there are still intercrystalline microcracks on the crystal surface of NCM, especially after the nickel content exceeding 60%. 48,49 Moreover, residual lithium compounds (e.g., LiOH, LiHCO 3 and Li 2 CO 3 ) may be formed on the cathode surface in the cycling process of nickel-rich layer.…”
mentioning
confidence: 99%
“…[5][6][7][8] Many strategies have been proposed already to improve these degradation factors for the capacity fading of Ni-rich cathode materials. For example, it was widely reported that surface treatments with various coating materials, such as ZrO 2 , Li 2 WO 4 , LiBO 2 , and Li 2 SiO 3 etc., [9][10][11][12][13][14] give an excellent effect in suppressing the decomposition of electrolyte on the surface of cathode active materials and the inactivation of the surface structure by preventing direct contact between the electrolyte and the cathode active materials. Moreover, Han et al reported that NCM721 (LiNi 0.7 Co 0.2 Mn 0.1 O 2 ) within which B 2 O 3 was incorporated showed the improved cyclabilities by suppressing the crack propagation on high voltage.…”
mentioning
confidence: 99%